Subtextual Analysis through Hegelian Dialectics in 5 Seconds of Summer’s Good Girls - Rommel Utungga Pasopati; Erlis Hersetya Firda; Albert Wijaya Kusuma; Riska Dewi Ramadhani; Firdausy Alya Hasana; Khaled Ahmed Mohammed (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This article investigates patterns of Hegelian Dialectics in 5 Seconds of Summer’s song lyrics entitled Good Girl. The background of this study lies on such stereotypes whether new literary works may still contain philosophical ideas. The research question of this paper is whether 5 Seconds of Summer’s song lyrics entitled Good Girl can be analyzed through Hegelian Dialectics. Through qualitative method, this paper shows how the situation of the girl is covered by old and new knowledge in the scheme of thesis-antithesis-synthesis as theorized by G. W. F. Hegel. This approach emphasizes how traditional and modern understandings interact, highlighting how dynamic identity building is. Using explorative approach, the components of the song lyrics are discussed through subtextual understandings that Hegelian Dialectics may erode such stereotype and later shape another stigma as well. It is analyzed that the girl lives the stigma that a good girl is a nerd and should not have fun outside the house. The song lyrics then accentuate that a smart girl could also be a bad girl and it indeed breaks the stigma of a clever girl is always a good girl. In conclusion, the song lyrics show how ideas of a good and a bad girl are not that simple since those reflect complex situation between common, social, and even academic norms. By stating so, the novelty of this article is evident; such new literary works may still always contain certain philosophical presuppositions.